2007
DOI: 10.2190/1qt3-6707-6054-v042
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Graphical Analysis with Microcomputer-Based Laboratories to Implement Inquiry as the Primary Mode of Learning Science

Abstract: The laboratory-learning environment needs to become more exploratory and undergo a transformation from its traditional confirmatory role in the learning of science. This is necessary to effectively allow students to achieve scientific literacy. The availability of powerful tools for data collection and analysis provides an opportunity for students to engage in activities similar to those found in scientific work. An investigation of science teachers' use of microcomputer-based laboratories in inquiry-based act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Professional STEM educator development programs have a substantial impact on teacher awareness [37] and abilities relative to conducting inquiry and making predictions [38] by using authentic data from sensors. Maeng et al [39] investigated preservice secondary science teachers' technology-enhanced inquiry instruction and their developing Technological Pedagogical Content Knowledge (TPACK) in the context of a 2-year Master of Teaching program.…”
Section: Use Of Sensors In Stem Educationmentioning
confidence: 99%
“…Professional STEM educator development programs have a substantial impact on teacher awareness [37] and abilities relative to conducting inquiry and making predictions [38] by using authentic data from sensors. Maeng et al [39] investigated preservice secondary science teachers' technology-enhanced inquiry instruction and their developing Technological Pedagogical Content Knowledge (TPACK) in the context of a 2-year Master of Teaching program.…”
Section: Use Of Sensors In Stem Educationmentioning
confidence: 99%
“…While a number of studies have supported these claims, , particularly in the context of inquiry based learning, ,, overall the results of implementing MBL activities appear mixed and successful implementation of MBL activities appears to be a complex issue. , Studies exist which counter the suggested benefits concerning student understanding of graphs and the connection between the macroscopic and more abstract . Other prominent issues appear to be the possibility that students may watch uncritically as the computer “does all the work for them”, as well as students encountering difficulty using the computing devices themselves. , …”
Section: Introductionmentioning
confidence: 99%